High‐resolution ultrasound visualization of the subcutaneous nerves of the forearm: A feasibility study in anatomic specimens. Issue 5 (May 2014) - Moritz, Thomas; Prosch, Helmut; Pivec, Christopher H.; Sachs, Alexander; Pretterklieber, Michael L.; Kriechbaumer, Lukas; Happak, Wolfgang; Bodner, Gerd
ABSTRACT Introduction: The aim of this ultrasound‐anatomical study was to evaluate the ability of high‐resolution ultrasound (HRUS) to visualize and infiltrate small subcutaneous nerves of the forearm in anatomic specimens. Methods: Seven nonembalmed human bodies (4 men, 3 women; mean age at death, 60 years) were included in the study. Two investigators scanned the anatomic specimens using 15‐MHz and 18‐MHz HRUS transducers. The lateral, medial, and posterior antebrachial cutaneous nerves were scanned and interventionally marked with ink using HRUS‐guidance. Subsequently, dissections were performed to assess the anatomical correlation of HRUS findings. Results: All 3 nerves were identified consistently using HRUS. The precision of the ink‐markings was excellent, with good correlation with the small peripheral branches of all 3 nerves. Conclusions: HRUS can identify precisely the small subcutaneous nerves of the forearm and may aid in both diagnosis and therapy in cases of neuropathy. Muscle Nerve49: 676–679, 2014